2009
DOI: 10.1002/jmri.21671
|View full text |Cite
|
Sign up to set email alerts
|

Age dependence of T1 perfusion MRI‐based hemodynamic parameters in human kidneys

Abstract: Purpose: To determine the association between renal cortical perfusion parameters from T1-DCE magnetic resonance imaging (MRI) and age in human kidney. Results: Mean RBF, RVD, and MTT were 127 mL/min/100 mL (SD ϭ 81 mL/min/100 mL), 40 mL/100 mL (SD 23 mL/100 mL), and 22 sec (SD ϭ 9 sec). A significant moderately negative correlation was found between RBF and age (R ϭ Ϫ0.447, P ϭ 0.007), RVD and age (R ϭ Ϫ0.420, P ϭ 0.012). MTT and age did not show a significant correlation (R ϭ 0.017, P ϭ 0.924). Repeating thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Various models [1][2][3][4][5][6][7][8][9][10][11] have been proposed for analysis of renal filtration using DCE-MRI. A critical review [38] showed that none of the published methods was sufficiently e ISD of cortical perfusion is better (14%; see Table 2) f Mean parenchymal perfusion 0 RBF/2*V kid ; RBF01.1 l min [1,46] g Using Eq.…”
Section: Existing Mri Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various models [1][2][3][4][5][6][7][8][9][10][11] have been proposed for analysis of renal filtration using DCE-MRI. A critical review [38] showed that none of the published methods was sufficiently e ISD of cortical perfusion is better (14%; see Table 2) f Mean parenchymal perfusion 0 RBF/2*V kid ; RBF01.1 l min [1,46] g Using Eq.…”
Section: Existing Mri Techniquesmentioning
confidence: 99%
“…Dynamic imaging of renal uptake of a contrast agent is an established way of assessing renal physiology using nuclear medicine, dynamic computed tomography and magnetic resonance imaging (MRI), and estimation of quantitative parameters is possible [1][2][3][4][5][6][7][8]. Several reviews are available [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Given that many renal pathologies involve vascular and/or perfusion abnormalities, imaging methods that specifically provide robust, serial measurements of kidney hemodynamic status could be of great utility. Toward this end, several MRI methods, using either endogenous or exogenous contrast mechanisms, have demonstrated great promise for the noninvasive assessment of kidney perfusion and oxygen delivery (1)(2)(3)(4)(5)(6). However, the application of these methods has primarily been limited to humans, pigs, rabbits, and rats.…”
mentioning
confidence: 99%
“…However, traditional GFR can be inaccurate and does not decrease substantially with the onset and progression of renal cysts (4,8). MRI can be a valuable tool to assess renal function (34)(35)(36)(37)(38)(39). One study showed the decline of renal function with MRI-based GFR in polycystic kidneys (31).…”
Section: Study Comparisonmentioning
confidence: 99%